ANALISIS PENDUDUK BEKERJA DI KOTA BANJARMASIN - CANNY LESTARI LAROSA; KHAIRI PAHLEVI (PPJP Universitas Lambung Mangkurat, 2019)
Canny Lestari Larosa, (2018) Working Population Analysis in Banjarmasin City. Advisor: Khairi Pahlevi, S.Pi.M.Si. This study aims to analyze the working population in the city of Banjarmasin in 2002 s.d. 2016. The independent variables in this study are wages, economic growth, inflation and education level. The dependent variable is the working population in Banjarmasin City. The research method used is quantitative method using multiple linear regression analysis. The results showed that the variable wages, economic growth, inflation and education level simultaneously had a significant effect on the working population in the city of Banjarmasin. Partially, variables that significantly influence the working population in Banjarmasin City are wages, economic growth and education level.Keywords: Working Population, Wages, Economic Growth, Inflation, Level of Education.